IDENTIFIKASI DAN SIMULASI FAKTOR PENYEBAB CACAT PRODUK BOTOL KONTAINER DENGAN METODE SIX SIGMA PADA PT INDOVASI PLASTIK LESTARI - S. P., R. Phenter; Safa, Faisal (Industrial and Systems Engineering Assessment Journal (INASEA), 2004)
The purpose of quality control that is done by a company is to give a qualified product to costumer and keep the company image. The best quality control for this time is Six Sigma quality control that has a goal to get Defect Per Million Opportunity (DPMO) for 3,4 or 99,99966% from what the customer expected from the product. The purpose of this research is to identify a problem that have connection with quality and element that becomes the biggest Cost To Quality (CTQ) on container bottle production process using Six Sigma method.